ENVIRONMENTAL EDUCATION DURING TECHNICAL ACTIVITIES ON THE THIRD STAGE OF SCHOOL EDUCATION IN POLAND - Pytel, Krzysztof; Piaskowska, Małgorzata; Rowińska, Małgorzata (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Technical education, is mainly focused on exploring the world of technology, arising the technical conscious and discovering the world that surrounds us. But also is in touch with the development of knowledge and awareness of environmental education, and arising the environmental responsibility which is part of the world. This study describes the ecological issues in technical education and the need of creating them. These are the objectives of environmental education and all educational activities and educational content covering environmental protection. Specifying what content should be put there to create students the opportunity to explore additional knowledge about the world.